Service Quality and Customer Loyalty in Malaysian Islamic Insurance Sector Exploring the mediating effects of Customer Satisfaction - Ariff Syah Juhari; Muhammad Awais Bhatti; Shishi Kumar Piaralal (2016)
The purpose of this study is to explore the mediating role of customer satisfaction between service quality dimensions and customer loyalty in Malaysian Islamic insurance sector. Based on the literature, six service quality dimensions were used to develop theoretical understanding about customer satisfaction and loyalty. This study proposes and tests a framework via structural equation modeling (Amos-16). The results of the analysis indicated that four of six service quality dimensions (tangible, responsiveness, fairness, and reliability) positively influence customer satisfaction which further influences customer loyalty. In other words, customer satisfaction mediates the relationship between four of six service quality dimensions (tangible, responsiveness, fairness, and reliability) and customer loyalty. Only two service quality dimensions (assurance and empathy) were not significantly related with customer satisfaction and loyalty. The findings further suggest that fairness have strongest effect on customer satisfaction and loyalty. The result of the study will help the managers and professionals to better understand how customer perceive service quality dimension and how these service quality dimensions are important for customers as well as for the organization. The study tested the impact of service quality dimensions on customer satisfaction and customer loyalty and found that tangibility, responsiveness, reliability, and fairness positively influence customer satisfaction. Therefore, the result of the study will help managers and professionals about how to deal with the customers to maximize the organizational profit. The result of the study suggested that fairness have strong influence on customer satisfactions and managers should pay attention on the fairness to improve service quality and maximize the customer satisfaction. As per our best knowledge, the suggested model and Islamic insurance sector have never been investigated before. (Abstract by authors)